Iconic logics? Plastic semiotics and Iconic Turn - Mengoni, Angela (E|C, 2020)
The paper explores the relationship between the so-called Iconic Turn by Gottfried Boehm and the visual semiotics developed by Algirdas Greimas. Beyond a focus on the explicit quotation of semiotic concepts or authors, the paper proposes to examine the heuristic approach to the image that characterizes both the analytical dimension of the Bildkritik and the semiotics of the image developed by the French generative semiotics. Taking into account the immanent approach of both traditions and some key-operators (such as “iconic difference” and “sémiotique plastique”), the acknowledgement of an active sense-generating capability of the “visual” will emerge as a common feature.